Brain‐derived neurotrophic factor haploinsufficiency impairs high‐frequency cortical oscillations in mice. (6th November 2017) - Jones, Nigel C.; Hudson, Matthew; Foreman, Joshua; Rind, Gil; Hill, Rachel; Manning, Elizabeth E.; van den Buuse, Maarten
Abstract: Schizophrenia is a complex psychiatric disorder with a heterogeneous aetiology involving genetic and environmental factors. Deficiencies in both brain‐derived neurotrophic factor (BDNF) and NMDA receptor function have been implicated in the disorder and may play causal and synergistic roles. Perturbations in the regulation of electrophysiological signals, including high‐frequency (γ: 30–80 Hz and β: 20–30 Hz) neuronal oscillations, are also associated with the disorder. This study investigated the influence of BDNF deficiency and NMDA receptor hypofunction on electrophysiological responses to brief acoustic stimuli. Adult BDNF heterozygote (BDNF +/− ) and wild‐type littermate C57Bl/6J mice were surgically implanted with EEG recording electrodes. All mice underwent EEG recording sessions to measure ongoing and auditory‐evoked electrophysiological responses following treatment with MK‐801 (0.3 mg/kg ip) or vehicle. Western blotting on post‐mortem cortical tissue assessed parvalbumin and GAD67 expression – markers of interneurons which are involved in the generation of gamma oscillations. Compared with wild‐type controls, BDNF +/− mice exhibited markedly dampened electrophysiological responses to auditory stimuli, including reductions in the amplitude of multiple components of the event‐related potential and auditory‐evoked oscillations, as well as reduced ongoing cortical gamma oscillations. MK‐801 elevated ongoing gamma power but suppressed evoked gamma power, and this was observed equally across genotypes. BDNF +/− mice also displayed reductions in parvalbumin, but not GAD67 expression. We conclude that reduced BDNF expression leads to impairments in the generation of high‐frequency neural oscillations, but this is not synergistic with NMDA receptor hypofunction. Reduced parvalbumin expression associated with BDNF haploinsufficiency may provide a molecular explanation for these electrophysiological deficits. Abstract : This murine study investigates the influence of BDNF deficiency and NMDA receptor hypofunction on electrophysiological cortical responses to brief acoustic stimuli. Dramatically dampened high‐frequency oscillations were identified in BDNF +/− mice, but these effects did not synergize with NMDA receptor antagonist treatment. These oscillatory findings were associated with down regulation of parvalbumin expression in BDNF deficient mice.